Effect of Gamma Radiation on Survival and Fertility of Male Anopheles stephensi Liston, Irradiated as Pharate Adults - Baruah; Lokendra Singh, Kavita Yadav, Sunil Dhiman* Indra (Journal of Ecobiotechnology, 2010)
Effect of radiations on the survival and fertility of male Anopheles stephensi Liston was evaluated in the laboratory with 70 and 100 Gy radiation dose. Irradiation of pharate adults with 100 Gy dose resulted in reduced emergence and longevity as compared to control (0 Gy) and 70 Gy dose. Fecundity and fertility of female An. stephensi mated with male irradiated as pharate adults was determined upto four blood meals. Significant decline was observed in fecundity after each blood meal at 100 Gy as compared to 0 Gy and 70 Gy irradiation. Similarly, the fertility was also decreased after each blood meal at 100 Gy irradiation. The present study indicates the suitability of 100 Gy dose for irradiation of pharate adult stage of mosquito as a part of mosquito management. ——————————————————————————————————– Defence Research Laboratory, Tezpur, India *Corresponding author, Email: dhiman_81@ indiatimes.com Please Cite This Article As: Kavita Yadav, Sunil Dhiman Indra Baruah and Lokendra Singh. 2010. Effect of Gamma Radiation on Survival and Fertility of Male Anopheles stephensi Liston, Irradiated as Pharate Adults. J. Ecobiotechnol. 2/4:06-10. Â